Chinese muslims and the conversion of the Nusantara to Islam - Wain, A (2015)
This thesis is a comprehensive re-examination of Maritime Southeast Asia's (or the Nusantara's) Islamic conversion history between the late thirteenth and early seventeenth centuries. Traditionally, academia has attributed this event to Muslim traders and/or Sufis from either India and/or the Middle East. During the late twentieth century, however, a number of scholars began to consider the possibility of Chinese Muslim involvement. The resulting discussions focused on a re-evaluation of Javanese history in the context of attempts to re-conceptualise pre-modern Nusantara trade (considered the catalyst for Islamisation) as fundamentally orientated towards Southern China, where Muslims played a significant commercial role from the seventh through to the early fifteenth centuries. Despite the intrinsic merits of these efforts, however, they have all been limited by an overwhelming focus on Java and a tendency to examine the relevant issues over only a very narrow time span. This thesis seeks to rectify these problems. First, it will evaluate the validity of the new commercial framework over a much longer period – from the rise of Śrīvijaya in the seventh century CE to the establishment of the early seventeenth-century European trade monopolies. This longue dureé view will provide a much stronger basis for both conclusively re-orientating pre-modern Nusantaran trade towards China and also positing it as the catalyst for conversion, with Chinese Muslims at its heart. Second, the thesis will look beyond Java to examine the conversion histories of several other important Nusantara locations (Samudera-Pasai, Melaka and Brunei), as accessed through early written texts (indigenous, European and Chinese) and archaeology. The thesis then, and thirdly, couples this examination with a consideration of the Islamic influences which came to bear on the Nusantara’s early intellectual and architectural expressions of Islam. Ultimately, by taking this broad chronological, geographical and cultural approach, the thesis aims to more reliably assess the possibility that Chinese Muslims influenced the Nusantara’s initial Islamisation process.